ASUHAN KEPERAWATAN DENGAN PENDEKATAN TEORI MODEL ADAPTASI ROY PADA PASIEN CONGESTIVE HEART FAILURE: CASE STUDY - liniyarti, Liniyarti; Herawati, Tuti (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
Congestive Heart Failure (CHF) is a chronic complex syndrome characterized by the inability of the heart to support the circulation of the peripheral organs and may cause negative effects on the whole human body systems. CHF survivors may develop poor adaptation and quality of life also death. Roy's adaptation theory model-based intervention aid in improving patient adaptation to the fulfillment of physiological needs, self-concept, role function, and interdependence. The purpose of this case study was to apply Roy's adaptation theory model to patients with CHF. The results showed that adaptive mal behavior becomes the priority problem of low cardiac output with focal stimuli: increased afterload, preload, contractility, and changes in heart rate. The history of hypertension, diabetes mellitus, and non-adherence were included in the contextual stimulus. The history of smoking is included in the residual stimulus. Two mechanisms of regulatory and cognitive control are used as nursing interventions. Results showed that the patient performed physiological-physical adaptation had no diuretic injection, was capable to endure fluid restriction, and showed adequate fluid balance. Moreover, patients were also adapted with lifestyle changes supported by their families. It is recommended to provide Roy's adaptation theory model-based nursing intervention to the chronic disease patients in the clinical setting.